2023
DOI: 10.3390/ma16072581
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Coatings Based on Calcium Phosphate and Their Effect on Cytocompatibility and Bioactivity of Titanium Nickelide

Abstract: Coatings based on calcium phosphate with thicknesses of 0.5 and 2 μm were obtained by high-frequency magnetron sputtering on NiTi substrates in an argon atmosphere. The coating was characterized using X-ray diffraction, scanning electron microscopy, atomic force microscopy, and in vitro cytocompatibility and bioactivity studies. A biphasic coating of tricalcium phosphate (Ca3(PO4)2) and hydroxyapatite (Ca10(PO4)6(OH)2) with a 100% degree of crystallinity was formed on the surface. The layer enriched in calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…A biofilm, enriched with precipitated Ca and P as a result of exposure to CPP-ACP, might act as a protective layer and reduce the surface Ni content of orthodontic wire. The ongoing development of novel calcium phosphate coatings for NiTi alloys aimed at biomedical application [38][39][40] underscores the potentially protective and anticorrosive nature of CPP-ACP. The use of CPP-ACP holds promise for application as a safe anticariogenic alternative to fluoride in orthodontic patients, acting as a chemoprophylactic agent with anticorrosion properties.…”
Section: Discussionmentioning
confidence: 99%
“…A biofilm, enriched with precipitated Ca and P as a result of exposure to CPP-ACP, might act as a protective layer and reduce the surface Ni content of orthodontic wire. The ongoing development of novel calcium phosphate coatings for NiTi alloys aimed at biomedical application [38][39][40] underscores the potentially protective and anticorrosive nature of CPP-ACP. The use of CPP-ACP holds promise for application as a safe anticariogenic alternative to fluoride in orthodontic patients, acting as a chemoprophylactic agent with anticorrosion properties.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that a Zn-1.5 Mg alloy was treated in a supersaturated calcium-phosphorus solution at 37 • C for 14 days, which resulted in the formation of a protective layer of calcium-rich phosphate on the alloy surface, and that cell viability and adhesion were significantly enhanced when U-2 OS cells were cultured on the calcium phosphate-protected film [16]. In another study, CaP coatings were prepared by high-frequency magnetron sputtering, and it was found that bone marrow mesenchymal stem cells (MSCs) adhered well to the coating surface and showed good proliferation [24]. In an in vivo study of CaP coatings prepared on zinc alloy surfaces, no significant inflammatory or adverse reactions were observed around the implants.…”
Section: Introductionmentioning
confidence: 99%